PINK1-dependent phosphorylation of Serine111 within the SF3 motif of Rab GTPases impairs effector interactions and LRRK2-mediated phosphorylation at Threonine72. Issue 9 (11th May 2020) - Vieweg, Sophie; Mulholland, Katie; Bräuning, Bastian; Kachariya, Nitin; Lai, Yu-Chiang; Toth, Rachel; Singh, Pawan Kishor; Volpi, Ilaria; Sattler, Michael; Groll, Michael; Itzen, Aymelt; Muqit, Miratul M. K.
Abstract : Loss of function mutations in the PTEN-induced kinase 1 (PINK1) kinase are causal for autosomal recessive Parkinson's disease (PD) whilst gain of function mutations in the LRRK2 kinase cause autosomal dominant PD. PINK1 indirectly regulates the phosphorylation of a subset of Rab GTPases at a conserved Serine111 (Ser111) residue within the SF3 motif. Using genetic code expansion technologies, we have produced stoichiometric Ser111-phosphorylated Rab8A revealing impaired interactions with its cognate guanine nucleotide exchange factor and GTPase activating protein. In a screen for Rab8A kinases we identify TAK1 and MST3 kinases that can efficiently phosphorylate the Switch II residue Threonine72 (Thr72) in a similar manner as LRRK2 in vitro . Strikingly, we demonstrate that Ser111 phosphorylation negatively regulates the ability of LRRK2 but not MST3 or TAK1 to phosphorylate Thr72 of recombinant nucleotide-bound Rab8A in vitro and demonstrate an interplay of PINK1- and LRRK2-mediated phosphorylation of Rab8A in transfected HEK293 cells. Finally, we present the crystal structure of Ser111-phosphorylated Rab8A and nuclear magnetic resonance structure of Ser111-phosphorylated Rab1B. The structures reveal that the phosphorylated SF3 motif does not induce any major changes, but may interfere with effector-Switch II interactions through intramolecular H-bond formation and/or charge effects with Arg79. Overall, we demonstrate antagonistic regulation between PINK1-dependent Ser111 phosphorylation and LRRK2-mediated Thr72 phosphorylation of Rab8A indicating a potential cross-talk between PINK1-regulated mitochondrial homeostasis and LRRK2 signalling that requires further investigation in vivo .